Removal of Chromium and Lead from water through biomineralization - Poddar, Dhruv (My University, 2023)
Heavy metal contaminants present in the environment can enter the human body through the food chain and water contamination. The accumulation of heavy metals can lead to various health problems such as problems in the functioning of the brain, lungs, kidneys, liver, and other vital organs of the human body, which can lead to cancer, cardiovascular and neurological diseases, liver damage, and central nervous system disorders and other related diseases. In the present study, heavy metals such as Chromium (Cr) and Lead (Pb) were removed through biomineralization by using Bacillus sp. CT5. Biomineralization is the process by which organisms secrete inorganic minerals in the form of carbonate. Bacillus sp. CT5 can hydrolyze urea by producing urease enzyme. The isolate has high urease production that is 670.71 U/ml. It can survive a temperature range of 25-55o C and can also grow in a pH range of 6-11. Heavy metal removal was tested at different concentrations of Cr (1.36 μM,1.7 μM, 2.04 μM) which was 71.95%, 87.24% and 87.80% respectively. Pb samples were also tested for assessing the removal. The concentrations at which test was performed were 1.27 μM, 1.59 μM, 1.91 μM and removal efficiency was 99.57%, 99.69% and 99.08% respectively. Through biomineralization, heavy metal gets captured in the lattice sites of crystals of calcium carbonate by the formation of heavy metal calcium carbonate complex. The production of a heavy metal-calcium carbonate complex was also demonstrated by the FESEM and EDS data, indicating that the heavy metals were effectively immobilized by microbially induced calcium carbonate precipitation. This study shows biomineralization is an effective technique to remove heavy metals from contaminated sources.
M.Sc. Thesis
Keywords: Bacillus sp; biomineralization; Chromium; Lead; heavy metals